Data Envelopment Analysis for Determining the Efficiency of Variant Solutions for Traffic Flow Organisation - Budimir, Damir; Šoštarić, Marko; Vidović, Krešimir (Promet - Traffic&Transportation, 2019)
There is a small number of empirical modelling study cases available that are related to the calculation of variant solutions efficiency from the aspect of sustainable mobility in the urban areas. In practice, it is often necessary - especially when it comes to the urban transport network - to evaluate the solutions for traffic flow organisation and routing, in order to implement the one(s) with the maximum potential to reduce the possibility of congestion during peak travelling periods i.e. during transport network peak load. The paper presents an approach to the aforementioned problem by the application of the transport system efficiency analysis. The aspect of traffic flow organisation and routing efficiency in variant solutions is clarified through the analysis model development, built on the premises of Data Envelopment Analysis (DEA) method and the principles of unnecessary traffic flow intersections (TFI) theory. The proposed model defines the efficiency limit for data attributed to variant solutions, based on the calculation of the optimal TFI model and the possibilities of DEA method that include comparison and definition of relative routing efficiency for every optional traffic flow against the efficiency limit (optimal model) in order to calculate relative efficiency in relation to other solutions.